Differential microRNA expression for diagnosis and prognosis of papillary thyroid cancer - Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Paz-Cruz, Elius; Tamayo-Trujillo, Rafael; Zambrano, Ana Karina (Frontiers in Medicine, 2023)
Papillary thyroid cancer accounts for 85% of thyroid cancer. The diagnosis is based on ultrasound methods and tumor biopsies (FNA). In recent years, research has revealed the importance of miRNAs, non-coding RNA molecules that regulate gene expression and are involved in many diseases. The present mini review describes upregulated and downregulated miRNAs expression in papillary thyroid cancer patient samples (tissue, serum, plasma) and the genes regulated by these non-coding molecules. In addition, a bibliographic search was performed to identify the expression of miRNAs that are common in tumor tissue and blood. The miRNAs miR-146b, miR-221-3p, miRNA 222, miR-21, miR-296-5p, and miR-145 are common in both tissue and bloodstream of PTC patient samples. Furthermore, these miRNAs regulate genes involved in biological processes such as cell differentiation, proliferation, migration, invasion, and apoptosis. In conclusion, miRNAs could potentially become valuable biomarkers, which could help in the early diagnosis and prognosis of papillary thyroid cancer.